Epidemiological aspects and temporal trend of HIV/AIDS in women under antiretroviral treatment, general fields: 2002-2017 (Research, Society and Development, 2021)
Background and Objectives: In 2009, 4,737 cases of HIV / AIDS were reported in women in Brazil. Due to the greater vulnerability experienced by women, studies show that in underdeveloped countries such as Africa, young women between the ages of 15 and 24 have twice the likely to be living with HIV / AIDS when compared to men. In view of the above, the objective of the present study was to describe the epidemiological aspects and the temporal trend of HIV / AIDS in women in antiretroviral treatment in the General of Paraná fields from 2002 to 2017. Methods: This is a cohort epidemiological study (SAE) of the Municipality of Ponta Grossa - PR, in the period from 2002 to 2017. Data were collected from 504 medical records and records of reports of the aggravation of women receiving antiretroviral treatment in the city. Results: The cohort women were mostly white, with an average age of 45 years and with low schooling. There was a predominance of married women with heterosexual behavior who acquired the sexually transmitted infection. An association between sexual behavior, marital status and mode of transmission was observed, with an increase in the incidence of women living with HIV / AIDS in the municipality, with a growth of 1.35% per year and a higher incidence rate in 2016. Conclusion: It is It is important that public policies aimed at reducing gender inequality and actions that enable female empowerment be implemented in order to guarantee a reduction in the stigma suffered by these women.